Bt GS57 Interaction With Gut Microbiota Accelerates Spodoptera exigua Mortality - Li, Yazi; Zhao, Dan; Wu, Han; Ji, Yujie; Liu, Zhaorui; Guo, Xiaochang; Guo, Wei; Bi, Yang (Frontiers in Microbiology, 2022)
The Beet armyworm Spodoptera exigua (Lepidoptera: Noctuidae, Spodoptera) is an important global polyphagous pest. Pathogen infection could destroy the intestinal microbial homeostasis of insects, leading to the death of the host. However, the effect of the host intestinal microbial community on the insecticidal effect of Bacillus thuringiensis is rarely studied. In this study, the genome characteristics of Bt GS57 and the diversity and functions of the gut bacteria in S. exigua are investigated using crystal morphology, biological activity, and Illumina HiSeq high-throughput sequencing. The results showed that the Bt GS57 genome consists of 61 million raw reads with an average G+C content of 35.66%, with the Subreads N50 value of 9,339 bp. Furthermore, the Bt GS57 genome contains six cry genes: cry1Ca, cry1Da, cry2Ab, cry9Ea, cry1Ia, and cry1Aa, and a vegetative insecticidal protein gene vip3Aa. The Bt GS57 strain can produce biconical crystals, mainly expressing 70 kDa and 130 kDa crystal proteins. The LC50 value of the Bt GS57 strain against the S. exigua larvae was 0.339 mg/mL. Physiological and biochemical reactions showed that Bt GS57 belongs to B.t. var. thuringiensis. In addition, we found that B. thuringiensis can cause a dynamic change in the gut microbiota of S. exigua, with a significant reduction in bacterial diversity and a substantial increase in bacterial load. In turn, loss of gut microbiota significantly decreased the B. thuringiensis susceptibility of S. exigua larvae. Our findings reveal the vital contribution of the gut microbiota in B. thuringiensis-killing activity, providing new insights into the mechanisms of B. thuringiensis pathogenesis in insects.